(3GdHjFI h GdJfejI GdSjGMjIs - (3SdGe LYaQ(B, (3GdGSOjs; (3Ydj(B;(3cGXe CMeO(B, (3Rjf GdOjf(B;(3GdHWGWs ((3YeGf(B:s (3OGQ GdGjGe(B,s, 2014)
(3jVe GdHjFI hGdJdhK hGdedhKGJ GdHjFjI, CSGSjGJ GdSjGMI, GdSjGMI GdOjfjI aj cQHdGA GdebOSI, GdJfejI GdSjGMjI , GdJfejI GdSjGMjI GdeSJOGeI, GdJMOjGJ GdJi JhGLg GdJfejI GdSjGMjI(B.s
(3GdeQGLY U(B.191s
Keywords: (3GdHjFIs; (3GdJfejI GdHjFjIs; (3GdJfejI GdeSJOGeIs; (3JfejI GdSjGMIs